Pengaruh Stress Kerja terhadap Work Family Conflict pada Karyawati Bank Nagari Cabang Utama Padang - Lovery, Nathasya Permata; Nurmina, Nurmina (TSAQOFAH, 2025)
This study aims to identify whether job stress has an effect on work-family conflict among female employees at Bank Nagari, Padang City. The research is driven by the growing phenomenon of working mothers struggling to balance their professional responsibilities with their roles in the domestic sphere. A quantitative approach with a cross-sectional design was employed, involving 98 respondents selected through purposive sampling. Data were analyzed using a simple linear regression test. The results indicate a significant positive relationship between job stress and work-family conflict, with a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.117 suggests that job stress contributes 11.7% to the occurrence of work-family role conflict. The study concludes that higher levels of perceived job stress increase the likelihood of female employees experiencing conflict between professional and family roles. These findings highlight the importance of managerial policies and interventions aimed at promoting work-family balance for women in the banking sector.